Extensions of weakly supplemented modules - Alizade, Rafail; Büyükasik, Engin (MATHEMATICA SCANDINAVICA, 2008)
It is shown that weakly supplemented modules need not be closed under extension (i.e. if U and M/U are weakly supplemented then M need not be weakly supplemented). We prove that, if U has a weak supplement in M then M is weakly supplemented. For a commutative ring R, we prove that R is semilocal if and only if every direct product of simple R-modules is weakly supplemented.